Numerical investigation of the lower airway exposure to indoor particulate contaminants. Issue 4 (April 2020) - Hvelplund, Malthe H.; Liu, Li; Frandsen, Kirstine M.; Qian, Hua; Nielsen, Peter V.; Dai, Yuan; Wen, Leitao; Zhang, Yingqi
Inhalation exposure to indoor particulate contaminants contributes as one of the leading threats to public health. Most existing airway morphometry models are either theoretical or semi-empirical; these are developed for predicting deposition fractions for an averaged general population subgroup. It is difficult to customize a fast and accurate prediction on individual basis. This study aims to analyse the regional particle deposition along an anatomically correct airway model, which is developed from a healthy volunteer's computer tomography images. Computational fluid dynamics simulation results show that the majority of particles are deposited in the bronchi. Accumulation particles (0.1–2.0 μm) have the smallest deposition fraction in the lower airways. An increase in the aerodynamic diameter >2.0 μm of the particles elevated the deposition fraction. These findings inspire future investigations into control methods that minimize the negative health impact of indoor emissions.